An Analytical Study on Nuclear Weapon Testing, Controlling and Eliminating the Use of Nuclear Weapons - Priyadarshani,H.E.N.; Samarawickrama,R. (General Sir John Kotelawala University, Ratmalana, 2015)
The weapons used for mass destruction can be identified as Nuclear, Biological and Chemical (NBC). The controlling, reduction and eventual elimination of the use of nuclear weapons are analyzed as the main objective of the international community. According to world history there is only one such example, that is the Nuclear Weapon US used against Japan in World War II, which is in the history of physical warfare. There were many nuclear testing done during the cold war and they were carried out at maximum safety levels. Their intention and outcome were not physical conflicts. Many countries have used nuclear explosions to display nuclear capability. With the advancement of modern technology, destruction of human and physical resources would increase in a massive scale in comparison with the past. The main objectives of this research are, to identify the effects of nuclear weapons, analyze the use and their function to find information on the treaties on nuclear weapons and their practical application. The research question is on why powerful countries put much effort to develop their nuclear strength despite being in agreement to reduce the use of nuclear weapons. This research is based on secondary data. As for limitations, complete dependence on secondary data sources and the inability to identify countries that possess nuclear energy can be stated. The outcomes would enable us to show the effort of powerful countries to enhance their nuclear capability considering their differences in the international politics, lack of practicality in treaties agreed upon and absence of mechanism to effectively enforce those treaties. Due to these conditions banning nuclear testing and controlling and eliminating nuclear weapons have not become a reality yet. We can see that the powerful nations of the world continue with discussions to ban nuclear weapons. Hence it can be identified as a root cause in aggravating the conflicts in the arena of international politics.
Keywords: Nuclear Weapons; Mass Destruction; World Politics